Security Alarm for Motorcycle - Ismail Ismail; Yulia Yulia; Zulfalina Zulfalina (PSI-Aceh, 2015)
A security alarm for motorcycle has been developed. This equipment consists of two parts. Part one is as a remote control, where it produces a radio signal with frequency of 37.5 MHz to turn on (activate) or to turn off alarm. Part two consists of sensor, receiver to receive signal from part one, and alarm. This part two will be attached to motorcycle while part one will be kept as a key by the owner of motorcycle. This equipment has been tested in the laboratory and it worked well. When part two is activated by pushing the “set button” in part one, then any movement of part two (as a movement of motor cycle) by about 20 cm from initial position will cause the alarm sounds continuously. The alarm will be off whenever the “reset button” in part one is pushed. Part one (a remote control) can activate part two with a maximum of twelve meter separation apart. This shows that the equipment can be used as a security alarm to prevent the motorcycle to be stolen in the future.